The Sociocultural Image of the Clerical Staff of the Provincial Institutions of Western Siberia in 1895-1917 - D. V. Andriyanova (Научный диалог)
The article is devoted to the characterization of the collective portrait of the lower bureaucracy of the West Siberian provincial institutions in 1895-1917. The relevance of this topic is caused by the constant search for the best ways to transform gubernatorial power and recruitment. A representative source base is used for both published and unpublished materials from the State Archive funds of Tobolsk and Tomsk. It is shown that among the younger clerical staff, trends characteristic of the entire bureaucratic apparatus of the Russian Empire were observed: an increase in the number of “professional” officials, a general increase in the educational level and rejuvenation of the staff. It is noted that, despite this, until 1917, the problem of the extremely “modest” financial support of the offices remained unresolved. It is indicated that the sums allocated for hiring lower servants had not changed since the mid-90s of the 19th century, and the events that took place in the country invariably increased the required living wage, which negatively affected the life of officials and their families, they were actually on the verge of survival. It is concluded that this state of affairs was for young clerical staff only an additional incentive for professional growth and further career aspirations.